Interprofessional education - structural and didactical challenges / Interprofessionelles Lehren, Lernen und Handeln - Strukturelle und didaktische Herausforderungen - Handgraaf Marietta; Dieterich Sven; Grüneberg Christian (Sciendo, 2016)
After five years of experience in interprofessional education (IPE) in the Bachelor programs occupational therapy, midwifery, nursing, speech therapy, and physiotherapy at the University of Applied Sciences in Bochum (Germany), we have systematically evaluated and substantially revised our IPE concept in 2014/15. The structural and curricular embedding of IPE throughout the course of the five Bachelor programs requires the development and ongoing evolution of a binding concept for the interprofessional competence development. This concept needs to be based on a systematic reflection of current practice and sound scientific knowledge concerning interprofessional topics. Furthermore, it needs to address the promotion of competencies to act inter- and transprofessionally to enable a high quality of care (Wissenschaftsrat, 2012; Walkenhorst, 2012). Results of narrative literature reviews, structured internal discussions, interviews of experts and various internal and external evaluations have been incorporated into a new conceptual framework for IPE. It has been shown that a revision of the structure, the temporal sequences of modules and the framework to facilitate interprofessional practice are essential steps for continuous development of interprofessional education. In addition, barriers and challenges are identified and discussed. Overall, the process of development has been coordinated and accompanied continuously and successfully by an IPE committee involving different groups of representative members from the Department of Applied Health Sciences.